Analisis Miskonsepsi Mahasiswa dalam Menyelesaikan Soal Sistem Persamaan Linier (SPL) Berdasarkan Tahapan Newman - Ek Ajeng Rahmi Pinahayu; Luh Putu Widya Adnyani; Nani Mulyani; Sriyono Sriyono (Journal on Education, 2023)
Analyzing students' misconceptions is very important to do to prevent a chain of concept errors in working on math problems. The purpose of this research is to analyze students' misconceptions in solving Linear Equation Systems questions based on Newman's Stages. This type of research uses qualitative research. The subject is a semester IV student in the Informatics Engineering study program who is taking Linear and Matrix Algebra courses in Even Semester 2020/2021. There are 3 subjects as respondents which are symbolized by MKT, MKS, and MKR. The instruments used include observation, tests, documentation and interviews. The test used is the material system of linear equations (SPL). After the tests were carried out, observations were made according to Newman's stages. Furthermore, interviews were carried out and then triangulation of the data obtained. The results of the analysis of student misconceptions based on Newman's Stages are that the subject of MKT makes reading errors, comprehension errors, transformation errors and encoding errors. MKT subject misconceptions occur in MKT subjects because they are wrong in writing symbols, so that they continue to write conclusions. Furthermore, the MKS and MKR subjects made five errors at the Newman stage, namely reading errors, comprehension errors, transformation errors, process skill errors, and encoding errors. This happened among others due to errors in symbols, calculation errors and incomplete calculations, as well as errors in applying the Gauss Elimination method.